FINANCIAL REVENUE–EXPENDITURE PERFORMANCE AT KY HOA MEDICAL CENTER, 2022–2024 (Vietnam Journal of Community Medicine, 2026)
Objective: Research on the results of financial revenue and expenditure activities at Ky Hoa Medical Center in the period of 2022 - 2024. Research Methods: Quantitative research design using secondary data on the financial performance of the Center. Results and Conclusion: Total revenue includes revenue from medical examination and treatment activities and from other sources of revenue. The Center's total revenue increases steadily over the years, from 85,370 million VND in 2022 to 106,988.9 million VND in 2024. Revenue from medical examination and treatment accounts for 98.5 - 98.9% of total revenue, of which revenue from health insurance medical examination and treatment activities accounts for the majority and increases steadily from 61.2 - 67.9% and plays a fundamental role in the Center's revenue structure. Revenue from medical examination and treatment outside of health insurance is not stable, fluctuating from 30.8 - 37.7% of total revenue. Total expenditure tends to increase, from VND 78,448.7 million in 2022 to VND 98,610.9 million in 2024. Regular expenditure is large, accounting for 99.6% of total expenditure. Two major expenditure items: professional expenses (accounting for 65%) and personal payment expenses (accounting for 23%). Expenditures for purchasing and depreciation of fixed assets are low. The difference between pre-tax revenue and expenditure remains positive and improves year by year, reflecting the ability to be financially autonomous and manage costs relatively effectively. The fund allocation situation according to the Center's internal regulations maintains a stable ratio with the Risk Reserve Fund (10%), Development Investment Fund (35%), Reward - Welfare Fund (30%) and Supplemental Working Capital/Return on Investment (25%).
Keywords: financial revenue–expenditure performance, Ky Hoa Medical Center.